2018
DOI: 10.1002/tea.21440
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inquiry‐based learning on the achievement goal‐orientation of grade 10 physical sciences learners at township schools in South Africa

Abstract: Due to apartheid policies, Black African learners in South Africa have been severely disadvantaged in school science. Despite policy changes to redress these historical imbalances, Black African learners continue to underperform in science. Previous research has identified motivation as a key factor that impacts performance. Achievement goal orientation is a construct of motivation that explains learning behaviour. In an attempt to address the problem of learner motivation, this study investigated the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…For example, contrary to the case with traditional science teaching, an argument‐based inquiry approach resulted in higher achievement for learners with disabilities (Taylor, Tseng, Murillo, Therrien, & Hand, ). Also, 5e (engagement, exploration, explanation, elaboration, and evaluation) inquiry‐based lessons resulted in increased goal orientation, an aspect of learner motivation (Mupira & Ramnarain, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, contrary to the case with traditional science teaching, an argument‐based inquiry approach resulted in higher achievement for learners with disabilities (Taylor, Tseng, Murillo, Therrien, & Hand, ). Also, 5e (engagement, exploration, explanation, elaboration, and evaluation) inquiry‐based lessons resulted in increased goal orientation, an aspect of learner motivation (Mupira & Ramnarain, ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding how teachers can enhance students' post-secondary education and career in STEM fields, teachers can modify their lesson plan by incorporating Trowbridge and Bybee's 5E model (Trowbridge and Bybee, 1996;Bybee et al, 2006): Engagement, Exploration, Explanation, Elaboration, and Evaluation. Ample evidence has shown the effect of 5E model on enhancing students' STEM academic performance (Lara-Alecio et al, 2012;Kim, 2016;Mupira and Ramnarain, 2018). To help strengthen students' STEM interests, Burke (2014) suggested to add "Enrichment" to the model.…”
Section: Discussionmentioning
confidence: 99%
“…Step 1: For the development of the survey, we examined literature on: (a) home learning environment research (e.g., Peterson et al, 2005;Urdan et al, 2007;Sad and Gurbuzturk, 2013;Ramsdal et al, 2015); (b) parental involvement (e.g., Chavira et al, 2016;Holmes et al, 2018) Kim, 2016;Mupira and Ramnarain, 2018). By further examining these studies, we could develop items addressing educational experiences in home and classroom environments as viewed and experienced by the students during home and/or classroom activities.…”
Section: Survey Implementationmentioning
confidence: 99%
“…They however, did not implement inquiry learning complaining of large class sizes, the rush to complete the curriculum, and lack of resources (Ramnarain & Hlatswayo, 2018). In another study at high school, the results showed that using inquiry learning considerably improved mastery goal-orientation as compared to the traditional direct didactic approach (Mupira & Ramnarain, 2018). Mastery in goal-orientation is essential for improved achievement.…”
Section: Eurasia J Math Sci and Tech Edmentioning
confidence: 99%